Fenologia da floração e rede de interação entre abelhas e plantas em uma área em processo de restauração florestal localizada em Araras-SP - Santos, Jussara Fernanda (Universidade Federal de São Carlos, 2012)
The most widely used in forest restoration projects is heterogeneous planting seedlings. This methodology was used in an area of one hectare in the restoration process implemented in 2009 on the campus of UFSCar Macaw. High values are invested in financial forest restoration especially when there is a need for planting seedlings, so the assessment and monitoring of restoration projects are legitimate concerns. Considering the importance of awareness of the availability of floral resources and ecological areas restored, and the importance of bees as pollinators in natural and agricultural areas, the overall objective of this study was to identify the pattern of flowering in the area in the restoration process, considering the period of three years after establishment. The specific objective was to evaluate the use of woody species by the community of bees visiting the flowers. To assess the availability of floral resources utilized a method of presence and absence and intensity index Fournier. Observations were made on flowers to collect the bees. It was built a network of qualitative interaction between species. This work was divided into two chapters, the first chapter deals with the characterization of the flowering phenology and plant species studied. The second chapter presents the richness of bee floral visitors observed during 2011 and describes the resources acquired by them at the time of visit, and presents the network of interactions among species. The phenological study enables to visualize the availability of flowers at certain times of the year, seven species were found planted with flowering, the period with greater timing and intensity was between January and March, the hottest season of the year and wet. There was a flowering woody species regenerating in the Solanum lycocarpum that in the colder months and dry was important for maintaining flowers in the area. We identified 20 species of bees that collected nectar and pollen. The network of interaction was 42.5% connectance and shown to be nested with heterogeny and indices T equal to 13.80 and NODF equal to 64.9. The two approaches are very important tools for monitoring and evaluating the availability of floral resources for bees visiting areas in the process of forest restoration.
Keywords: Reflorestamento; Recursos florais; Monitoramento; Interação inseto-planta; Floral resources; Monitoring; Ecological interaction; CIENCIAS AGRARIAS